The third revolution in the Chinese countryside - Garnaut, Ross; Kuo, Shu-tʻien; Ma, Guonan (Trade and development, 1996)
The first revolution in the Chinese countryside was the land reform after the proclamation of the People's Republic of China in 1949. The second was decollectivization of agriculture and shift to the household responsibility system as a basis for agricultural production. This set the scene for the freeing of markets for farm products and linking of domestic markets to international markets; this 1996 book explores this third revolution. The first section of this book covers the issues of poverty in China and feeding the population. The second section describes price reforms in agricultural markets in China. The next two parts discuss international and regional issues of China's agricultural economy. Finally, there are contributions on what institutional changes have been associated with the third agricultural revolution. The contributions are from a team of experts on the Chinese economy led by Professor Garnaut